The commonplacing section of an early modern Spanish commonplace book: a digital edition - Eastgate, T (University of Oxford, 2022)
This data set consists of 40 image files in TIFF format, and an XML file. These files were created as part of a Digital Editions course, run by the Taylor Institution Library, during Hilary Term 2022. The course required participants to create a digitised version of a text. This text is 40 pages from the Bodleian's MS. Spanish e. 9. The images of the original text were created by the Bodleian Libraries' Mediated Copying Service, and then converted to TIFF format by using 'Save as' in Preview. The XML file included here contains an encoded transcription of the original text, created and edited using Oxygen XML Editor, according to Text Encoding Initiative (TEI) guidelines.